In-situ synthesis of graphitic carbon nitride/iron oxide−copper composites and their application in the electrochemical detection of glucose. (1st March 2018) - Liu, Lin; Wang, Mandy; Wang, Chengyin
Abstract: A simple method was proposed for the synthesis of graphitic carbon nitride (g-C3 N4 )/iron oxide-copper nanostructures through a one-step pyrolysis of Cu3 [Fe(CN)6 ]2 and melamine. The iron oxide and copper nanostructures, derived from Cu3 [Fe(CN)6 ]2, were decorated onto g-C3 N4 nanosheets, which can effectively protect the resultant graphitic carbon nitride nanosheets from restacking. The derived Fe2 O3 and Cu nanostructures greatly enhance the electro-catalytic property of as-prepared composites. Three components including g-C3 N4 nanosheets, Fe2 O3 and Cu cooperatively enhance the electrochemical performance of non-enzymatic glucose detection. Modified electrodes based on g-C3 N4 /Fe2 O3 -Cu composites could detect glucose in the range of 0.6 μM─2.0 mM with a detection limit of 0.3 μM. The as-fabricated modified electrodes also demonstrated good stability and anti-interference performance. Graphical abstract: Image 1 Highlights: A simple method for synthesis of graphitic carbon nitride/Fe2 O3 -Cu composites. The proposed composites, with rich active groups, show good chemical activity. The resultant composites present excellent electrocatalytic oxidation of glucose. The as-fabricated electrode can detect glucose with good performance.